2017
DOI: 10.1177/2158244017707004
|View full text |Cite
|
Sign up to set email alerts
|

Places Change Minds: Exploring the Psychology of Urbanicity Using a Brief Contemplation Method

Abstract: An accruing body of research suggests that urban environments negatively affect mental health and well-being. It is thought that some of this so-called "urbanicity effect" can be explained by the perceived quality of the living environment. The two studies reported here used online survey methods to explore changes to self-reported psychological mechanisms thought to underpin mental health and well-being before and after participants briefly contemplated urban/rural or desirable/undesirable residential images.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…The UK’s Department of Communities and Local Government [ 13 ] acknowledged the high concentration of deprived areas in inner cities of the UK. However, the urbanicity effect has been found to exist even after statistically controlling for deprivation suggesting that other factors, including psychological responses to places, are part of the picture [ 11 ].There is also evidence to suggest a causal relationship between perceived social characteristics of place and risk of mental health difficulties [ 7 , 14 , 15 ] with most authors endorsing a cyclic relationship between the psychology of mental distress and the urban environment with place influencing people’s psychology and vice versa [ 16 19 ]. Taken together, these studies emphasise the inherently contextual nature of psychological responses to living environments and the close ties that exist between place characteristics and human wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…The UK’s Department of Communities and Local Government [ 13 ] acknowledged the high concentration of deprived areas in inner cities of the UK. However, the urbanicity effect has been found to exist even after statistically controlling for deprivation suggesting that other factors, including psychological responses to places, are part of the picture [ 11 ].There is also evidence to suggest a causal relationship between perceived social characteristics of place and risk of mental health difficulties [ 7 , 14 , 15 ] with most authors endorsing a cyclic relationship between the psychology of mental distress and the urban environment with place influencing people’s psychology and vice versa [ 16 19 ]. Taken together, these studies emphasise the inherently contextual nature of psychological responses to living environments and the close ties that exist between place characteristics and human wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…This supports previous research conducted by Nettle et al (2014), which reported that levels of social trust were lower and levels of paranoia higher in deprived neighborhoods, even among participants who were only briefly exposed to these environments. Collectively, these findings suggest a potential pathway whereby harsh observable aspects of the neighborhood environment (e.g., excessive litter, visible vandalism) affect perceptions of the area (i.e., low social cohesion), which in turn leads to paranoid ideation (Corcoran et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Empirical studies suggest that neighbourhood environments that are characterised by high levels of deprivation may confer increased risk for mental health difficulties. It seems that even brief or remote exposure to physical and social cues indicative of deprivation are associated with negative perceptions about the self and others (Corcoran, Mansfield, Giokas, Hawkins, Bamford, & Marshall, 2017). For example, Ellett, Freeman and Garety (2008) explored the acute effects of exposure to a deprived urban environment on the psychology of people experiencing persecutory delusions.…”
Section: The Neighbourhood Social Environment: the Impact Of Deprivationmentioning
confidence: 99%
See 1 more Smart Citation
“…The mental health impact of city dwelling has also received particular attention, shedding new light on the intimate, intensive, and potentially psychologically damaging experience of urban places at varying stages of development (Bhugra et al, 2019;Corcoran et al, 2017;Lederbogen et al, 2011;Vassos et al, 2012). Social science and humanities researchers have also provided extensive insights on social relations in the city as a public sphere, including how these shape emotional encounters, experiences of social isolation or connectedness, community cohesion, intercultural dialogue and affective politics (Amin, 2013;Richaud and Amin, 2019;Piekut and Valentine, 2017;Simonsen, 2007;Wilson, 2017).…”
mentioning
confidence: 99%